Different types of screen-based sedentary time and anxiety in adolescents: Video games may be more important - Chen, Sitong; Clark, Cain C. T.; Ren, Zhanbing (Frontiers in Public Health, 2022)
Purpose: Evidence has demonstrated the negative impact of excessive screen-based sedentary time (SSB) on adolescents’ mental health outcomes, including anxiety symptoms. However, little is known regarding the association between specific types of SSB and anxiety symptoms in adolescents. Thus, this study sought to explore the associations between specific types of SSB and anxiety symptoms in a sample of Chinese adolescents. Methods: A web-based questionnaire survey was used to collect data. 1998 study participants and their parents/guardians completed the survey. Of the 1998 study participants, 1331 study participants provided valid data pertaining to the variables of this study (response rate = 57.7%). SSB was categorized into TV/movie time, video games time, and other screen-based time. Anxiety symptoms were assessed using Zung Self-Rating Anxiety Scale, which has been confirmed as a validated assessment in Chinese youth populations. Generalized linear models were used to explore the associations between specific types of SSB and anxiety symptoms. Results: In adolescents overall, video games time was positively and significantly associated with anxiety symptoms (Beta = 0.52, 95% CI: 0.18-0.85, p < 0.005). This association was also observed specifically in boys (Beta = 0.52, 95% CI: 0.11-0.92, p < 0.05); however, in girls, only other screen-based time was significantly associated with anxiety symptoms. Conclusion: Specific SSB matters; indeed, interventions aiming for anxiety prevention should be designed based on limiting specific types of SSB in boys and girls. Future studies are encouraged to confirm the veracity of the findings in this study.